2013
DOI: 10.1007/s11606-013-2445-x
|View full text |Cite|
|
Sign up to set email alerts
|

Leg Pain in a Patient with Myasthenia Gravis

Abstract: K E Y W O R D S :No ca r di a ; m y a s th en ia g r a v is ; pre dn is on e; immunocompromised. J Gen Intern Med 28(11):1523 DOI: 10.1007/s11606-013-2445-x © Society of General Internal Medicine 2013A 79-year-old male with myasthenia gravis on chronic prednisone therapy presented with progressive left leg pain and swelling and nonproductive cough for one month. Physical examination was significant for multiple, irregular, tender areas of induration in his bilateral lower extremities without overlying erythema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…We performed the literature review by searching the MEDLINE database using the key words "nocardia," "nocardiosis, "and "myasthenia gravis." We found that up until our search, only 7 case reports of MG patients with nocardiosis had been reported [3][4][5][6][7][8][9]. To improve understanding of the disease process, we summarized the clinical characteristics of these patients, and these are listed in table 1.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the literature review by searching the MEDLINE database using the key words "nocardia," "nocardiosis, "and "myasthenia gravis." We found that up until our search, only 7 case reports of MG patients with nocardiosis had been reported [3][4][5][6][7][8][9]. To improve understanding of the disease process, we summarized the clinical characteristics of these patients, and these are listed in table 1.…”
Section: Discussionmentioning
confidence: 99%